Pemikiran Linguistik Sibawaih: Kajian I'rab - Sinta, Priti; Haniah, Haniah; Hamzah, Andi Abdul (Universitas Islam Negeri Alauddin, 2024)
This article discusses linguistic thinking in the study of i'rab. The purpose of writing this article is to provide an understanding related to sibawaih linguistic thinking. This article is a descriptive literature-based article. The results of this research are that Imam Sībawaih succeeded in developing the science of nahwu so that it is widely studied, he has works that are the main reference in the science of nahwu. Nahwu science is a scientific discipline that still has an attraction for Arabic language observers. The science of nahwu is one of the studies of Arabic grammar which discusses sentence structure and determining the final meaning of each word in Arabic, known as i'rab.